2020
DOI: 10.1111/maec.12585
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and geographical distribution of resting stages of eukaryotic algae in the surface sediments from the southern Chinese coastline based on metabarcoding partial 18S rDNA sequences

Abstract: Surface sediment samples were collected from sixteen sites of the southern Chinese coastline in this study. Diversity of eukaryotic microalgae was examined using high‐throughput sequencing of 18S rDNA to understand the community structure and geological distribution of microalgal resting stages. A total of 218 operational taxonomic units (OTUs) were detected for eukaryotic algae, and only 75 OTUs (34.40%) were detected into species level. The algal communities were composed of sixty‐four genera belonged to twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 80 publications
1
8
1
Order By: Relevance
“…Dinoflagellates also had the highest OTU richness. The algal community structure in this study is comparable to those reported in sediments from the other coastal sea areas based on metabarcoding analysis, in which dinoflagellate DNA reads and OTU richness were predominated ( Dzhembekova et al, 2018 ; Liu et al, 2020a ). Dinoflagellates have much higher DNA copies (up to thousands) than the other protists (dozens to hundreds) ( Lin, 2011 ), which may lead to their over-representation in metabarcoding studies.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Dinoflagellates also had the highest OTU richness. The algal community structure in this study is comparable to those reported in sediments from the other coastal sea areas based on metabarcoding analysis, in which dinoflagellate DNA reads and OTU richness were predominated ( Dzhembekova et al, 2018 ; Liu et al, 2020a ). Dinoflagellates have much higher DNA copies (up to thousands) than the other protists (dozens to hundreds) ( Lin, 2011 ), which may lead to their over-representation in metabarcoding studies.…”
Section: Discussionsupporting
confidence: 81%
“…A total of 3,899 eukaryotic OTUs including 454 algal OTUs were detected in the 30 surface sediment samples from the four sea areas along the southeast Chinese coasts in this study. The OTU richness in this study was much higher compared with those observed in surface sediments from other sea areas, for example 180 OTUs of microalgal species were identified from 13 stations across the Black Sea ( Dzhembekova et al, 2018 ), and 218 algal OTUs in 16 stations along the southern Chinese coast ( Liu et al, 2020a ). The results suggest that investigations in diverse sea areas may enhance the OTU richness.…”
Section: Discussioncontrasting
confidence: 61%
“…The potential AZP producer, Azadinium poporum, occurred in all stations except for those in the inner Jiaozhou Bay, and ranked the sixth most abundant cyst type (Figure 6). A. poporum was reported to distribute widely in surface sediments from the Chinese coasts (Gu et al, 2013;Liu et al, 2020;Tang et al, 2021), and 13 out of 16 strains of A. poporum from different geographic locations along the Chinese coastline contained AZPs (Krock et al, 2014). However, species in Azadinium has been seldom reported in the phytoplankton survey, which might be ignored due to their small Biecheleria halophila was the most abundant cyst type in sediments from the Qingdao coast in our study.…”
Section: Discussionmentioning
confidence: 59%
“…Biecheleria has become more frequently detected in the phytoplankton communities as the development of molecular biological techniques (Sundstrom et al, 2010). Taxa in Biecheleria generally form resting cysts (Moestrup et al, 2009), which made them common dominant eukaryotes in sediments based on metabarcoding analysis (Dzhembekova et al, 2018;Liu et al, 2020;Rhodes et al, 2020). B. halophila was reported to form a co-occurring bloom with Scrippsiella hangoei in the Baltic Sea (Kremp et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Many species of dinoflagellates form resting cysts and have different life cycles that consist of a cyst and motile stage. The genus Euduboscquella parasitises Tintinnids and produces cysts (Dolan et al 2013;Shang et al 2019;Liu et al 2020). The temporal dominance of Amoebophrya sp.…”
Section: Eukaryotic Communitymentioning
confidence: 99%